DISEÑO E IMPLEMENTACIÓN DE UN BANCO DIDÁCTICO DE PRUEBAS DE PLC - Hernández Ortiz, Michael Andrés (Universidad Antonio Nariño, 2024)
With this degree work, it is intended to reinforce the knowledge of the students of the Antonio Nariño University of the electronic engineering career, since within the professional field they must face different challenges, for this reason it is of vital importance to put into practice everything learned. As a result of this, it seeks to develop and implement a didactic PLC test bench where the objective is that it be mobile, easy to transport by teachers and students, it will consist of a briefcase and inside there will be a peripheral connection plate. of the PLC, this board will have the direct voltage digital input and digital output connections. At the top of the board, you will have a facility to mount the PLC, allowing it to remain fixed and easy to manipulate. Keywords: Electronic Engineering, Didactic Bank, Periphery, PLC.